2022
DOI: 10.1186/s13287-022-02941-w
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell transplantation in newly diagnosed type-1 diabetes patients: a phase I/II randomized placebo-controlled clinical trial

Abstract: Background Type-1 diabetes (T1D) occurs following autoimmune-induced pancreatic beta cells death. Among several treatment modalities, mesenchymal stem cells (MSCs) transplantation is promising for autoimmune disorders due to immunomodulation, regeneration, and migration to damaged tissue upon systemic injection. This study assessed the safety and efficacy of intravenous injection of autologous bone marrow-derived MSCs in newly diagnosed T1D patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 81 publications
1
17
0
2
Order By: Relevance
“…Autologous hematopoietic stem cell (AHSC) bone marrow (BM) transplantation (AHSC-BMT) can lead to complete and durable remission in patients with new-onset T1DM[ 15 - 18 ]. Moreover, confirming earlier studies, early autologous MSC transplantation in newly-diagnosed T1DM children is reported as a promising, safe, and effective treatment, significantly improving HbA1c and C-peptide levels and shifting pro-inflammatory cytokines to anti-inflammatory cytokines, ultimately mitigating hypoglycemic episodes[ 19 , 20 ]. In T2DM, Bhansali et al [ 21 , 22 ] showed that autologous BM-MSCs (BM-AMSCs) and autologous BM-mononuclear cells (BM-AMNCs) result in sustained reduction in insulin doses, with improvement in insulin sensitivity with MSCs and increase in C-peptide response with MNCs[ 21 - 23 ].…”
Section: To the Editorsupporting
confidence: 65%
“…Autologous hematopoietic stem cell (AHSC) bone marrow (BM) transplantation (AHSC-BMT) can lead to complete and durable remission in patients with new-onset T1DM[ 15 - 18 ]. Moreover, confirming earlier studies, early autologous MSC transplantation in newly-diagnosed T1DM children is reported as a promising, safe, and effective treatment, significantly improving HbA1c and C-peptide levels and shifting pro-inflammatory cytokines to anti-inflammatory cytokines, ultimately mitigating hypoglycemic episodes[ 19 , 20 ]. In T2DM, Bhansali et al [ 21 , 22 ] showed that autologous BM-MSCs (BM-AMSCs) and autologous BM-mononuclear cells (BM-AMNCs) result in sustained reduction in insulin doses, with improvement in insulin sensitivity with MSCs and increase in C-peptide response with MNCs[ 21 - 23 ].…”
Section: To the Editorsupporting
confidence: 65%
“…HbA 1C , fasting C-peptide and insulin requirement were not significantly different compared to the control group[ 107 ]. In contrast, Izadi et al [ 108 ] found improved HbA 1C and C-peptide levels, a reduced number of hypoglycemic events and increased anti-inflammatory patterns. Furthermore, early BM-MSC transplantation (< 1 year after disease onset) further improved HbA 1C levels and C-peptide levels compared to those who received the transplantation > 1 year after disease onset[ 108 ], similar to that of UC-MSC.…”
Section: Mesenchymal Stem Cell Therapy In T1dmmentioning
confidence: 93%
“…In a randomized, double-blind, phase I/II clinical trial, 11 patients with T1DM were treated with BM-MSCs, and the percentage of HbAc1 was significantly reduced at 12 months. Cytokine interleukin 4 (IL-4) and interleukin 10 (IL-10), which have anti-inflammatory effects, were significantly increased, while tumor necrosis factor-alpha (TNF- α ), which has proinflammatory effects, was significantly decreased [ 10 ]. Taken together, these results showed that the use of MSCs reduced HbAc1 and insulin requirements in T1DM patients, decreased the levels of signature antibodies against GAD and ZnT8 in T1DM patients, increased CP levels, and enhanced systemic anti-inflammatory capacity.…”
Section: Clinical Research Progress On Mscs As a Treatment For Dmmentioning
confidence: 99%